2022
DOI: 10.1136/bmjopen-2021-058197
|View full text |Cite
|
Sign up to set email alerts
|

Quality and reporting of patient-reported outcomes in elderly patients with hip fracture: a systematic review

Abstract: ObjectiveTo assess how patient-reported outcomes (PROs) are reported and to assess the quality of reporting PROs for elderly patients with a hip fracture in both randomised controlled trials (RCTs) and observational studies.DesignSystematic review.Data sourcesMedline, Embase and CENTRAL were searched on 1 March 2013 to 25 May 2021.Eligibility criteriaRCTs and observational studies on geriatric (≥65 years of age) patients, with one or more PRO as outcome were included.Data extraction and synthesisPrimary outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The basic information includes (1) title, (2) authors, (3) language, (4) year, (5) journal, (6) registration, (7) single or multicentre, (8) study location, (9) sample size, (10) have efforts to determine the sample size, (11) study types (non-inferiority or inferiority), ( 12) acupuncture modality (head acupuncture, body acupuncture, electroacupuncture, etc), ( 13) randomisation sequence generation, ( 14) randomisation allocation concealment mechanism, (15) randomisation implementation, (16) randomisation concealment, (17) blinding patient, (18) blinding operator, (19) blinding evaluator, (20) intervention time, (21) intervention frequency and (22) funding.…”
Section: Basic Characteristics Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic information includes (1) title, (2) authors, (3) language, (4) year, (5) journal, (6) registration, (7) single or multicentre, (8) study location, (9) sample size, (10) have efforts to determine the sample size, (11) study types (non-inferiority or inferiority), ( 12) acupuncture modality (head acupuncture, body acupuncture, electroacupuncture, etc), ( 13) randomisation sequence generation, ( 14) randomisation allocation concealment mechanism, (15) randomisation implementation, (16) randomisation concealment, (17) blinding patient, (18) blinding operator, (19) blinding evaluator, (20) intervention time, (21) intervention frequency and (22) funding.…”
Section: Basic Characteristics Extractionmentioning
confidence: 99%
“…The EQUATOR (Enhancing the QUAlity and Transparency Of health Research) network emphasised that only adequate reporting studies can provide reliable information and credible conclusions 4. But, the reporting quality of PROs in RCTs is of concern, van der Vet et al 18 found that 52.3% of RCTs did not provide the rationale for selecting PRO scales, 83.6% of RCTs did not mention missing data, while it was 44% and 72% in Brundage et al ’s study 19. Ambiguous reporting of PROs in RCTs limited the promotion and application of PRO results in clinical practices.…”
Section: Introductionmentioning
confidence: 99%